Methodological issues and prospects of semiotics of humour. - Gluscevskij, Dmitrij (Sign Systems Studies, 2017)
This article aims at proposing a way to identify humour by means of Greimassian semiotics and to single humour out as a unique object of semiotic analysis. Firstly, the article discusses the fundamental epistemological premises of semiotic text analysis through the analysis of texts by Greimas which were meant to further and legitimize his project of semiotics. Also, the already existing attempts at providing a semiotic definition of humour are critically evaluated while relating their problematic aspects with the implicitly defined field of semiotic interest. Finally, it is demonstrated that a productive semiotic description of a comic text is possible when the status quo epistemological views are revised and the traditional field of semiotic analyses is expanded accordingly.